Early to late summer fish distribution in a bay of the Gulf of Bothnia - Kagervall, Anders (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2008)
This study examined the fish community in a shallow bay in the Gulf of Bothnia during the summer of 2007. The distribution of several fishsh species within the bay was investigated. Possible influence on trout is discussed. Fish was sampled eight times at three different areas of the bay starting 4th of June and ending 7th of September. The fish was sampled with multimesh gillnets and horizontal echosounding. I found that the bay was dominated by three freshwater species, roach, perch and ruffe with no apparent effect of season on their distribution. However, the abundance of roach in the outer area changed significantly with low abundance early in the summer and high abundance late summer and autumn. The overall high abundance of warm water species in trout feeding areas could potentially have a negative effect on trout through feeding competition.